2019
DOI: 10.1080/21678421.2019.1612922
|View full text |Cite|
|
Sign up to set email alerts
|

A phase III trial of tirasemtiv as a potential treatment for amyotrophic lateral sclerosis

Abstract: Objective: To assess the efficacy of tirasemtiv, a fast skeletal muscle troponin activator, vs. placebo in patients with amyotrophic lateral sclerosis. Methods: VITALITY-ALS (NCT02496767) was a multinational, double-blind, randomized, placebo-controlled clinical trial. Participants tolerating 2 weeks of open-label tirasemtiv (125 mg twice daily) were randomized 3:2:2:2 to placebo or one of three target tirasemtiv dose levels, using an escalating dosage protocol lasting 28 days. The primary outcome measure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 15 publications
(19 reference statements)
0
42
0
Order By: Relevance
“…Clinical trials in ALS have in fact have evolved to be more efficient, with the most significant change being a transition from studies based on survival as a primary endpoint to measures based on function. [1][2][3][4] In addition, modeling studies and recent clinical trials have suggested that cohort enrichment to select for rapidly progressive patients may reduce sample size and trial duration. However, clinical trials still require many months to complete, and participants must travel to the study center frequently, limiting involvement to those in close proximity to study sites and who are not too debilitated to travel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials in ALS have in fact have evolved to be more efficient, with the most significant change being a transition from studies based on survival as a primary endpoint to measures based on function. [1][2][3][4] In addition, modeling studies and recent clinical trials have suggested that cohort enrichment to select for rapidly progressive patients may reduce sample size and trial duration. However, clinical trials still require many months to complete, and participants must travel to the study center frequently, limiting involvement to those in close proximity to study sites and who are not too debilitated to travel.…”
Section: Introductionmentioning
confidence: 99%
“…This variability in measurement mandates a sample size on the order of 120-150 per treatment arm in order to have sufficient power to appreciate a moderate effect size. 2,4 Variability in rates of decline with respect to any measure come from three major sources: 1. "noise" related to inevitable nondisease-related factors, such as subject motivation or fatigue (for clinical measures); 2. measurement error and inconsistencies due to the tool or technique itself or: 3. deviations from the assumption that ALS progresses in a linear manner.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics resemble those of most previous and current ALS trials, with the exception that time from first symptom to screening was 22.8 ± 19.1 months, which is longer than in many recent trials. (6,(11)(12)(13)(14) For some trials, symptom onset and not time since diagnosis was the basis of the inclusion criteria, which may contribute to at least some of the differences related to this patient characteristic. (11)(12)(13)(14) In addition, 113/457 (24.7%) of patients were on edaravone, either alone or in combination with riluzole.…”
Section: Resultsmentioning
confidence: 99%
“…As the lowest dose appeared to be active in all three key efficacy measures, this multiple contrast approach may not have been the best analysis to demonstrate a treatment effect of reldesemtiv versus placebo. Finally, this trial enrolled more slowly progressing patients than several recent trials (6,(11)(12)(13)(14), which may have somewhat diluted an efficacy signal by some patients not progressing appreciably during the relatively short 12-week duration of active treatment. Indeed, there appeared to be clear evidence of benefit of reldesemtiv among those patients progressing more rapidly prior to randomization and during the course of the trial.…”
Section: Discussionmentioning
confidence: 99%
“…A feature of the studies of tirasemtiv is a substantial incidence of side-effects, particularly dizziness, euphoria, fatigue and gait disturbances, and it is likely that these side-effects contributed to the deterioration in the 6 min walk. Tirasemtiv has also been evaluated for the treatment of amyotrophic lateral sclerosis, a neurodegenerative disease causing progressive weakness and death due to respiratory failure typically 3-5 years after diagnosis (Shefner et al 2019). This was a randomised, double-blind trial with placebo and three drug levels evaluated after 24 weeks.…”
mentioning
confidence: 99%